A cross-sectional analysis of post-acute COVID-19 symptoms - Perna, S.; Abdulsattar, S.; Alalwan, T. A.; Zahid, M. N.; Gasparri, C.; Peroni, G.; Faragli, A.; La Porta, E.; Ali Redha, A.; Janahi, E. M.; Rondanelli, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Objectives. The severe acute respiratory syndrome (COVID-19) due to SARS-CoV-2 was first reported in China in December 2019 and has generated a worldwide pandemic. The objective of the research is to examine and describe (a) the symptoms that persist after the end of the acute stage and (b) their relationship with the severity of the disease.Study Design. This study is a cross-sectional study conducted in the Kingdom of Bahrain on COVID-19 infected patients using an online survey questionnaire with a total number of 52 patient responses (29 females and 23 males).Method. A scale (0 no symptoms to 10 very high symptoms intensity) was assessed in patients after 3 months to detect the relevance of specific symptoms post-COVID-19 such as emotional and physical health, headache, dyspnoea, pain (muscles/joints/chest), anosmia, vertigo, neurologic symptoms, sarcopenia, delirium.Results. The most common COVID-19 symptoms were reported to be fever (69.2%), headache (59.6%), and cough (50.0%). Data analysis showed that BMI was not correlated with any post-acute COVID-19 symptoms. Regarding the post-acute COVID-19 symptoms, this study showed that an increase of intensity of headache was associated with an increase of delirium; an increase of intensity of dyspnoea was associated with an increase of pulmonary dysfunction. The increase of anosmia and dysgeusia was associated with an increase in delirium. In addition, the increase of neurological symptoms and delirium were associated with the increase of sarcopenia. The most common persistent post-COVID-19 symptoms observed in this study were emotional stress, followed by loss of smell and taste, and neurological symptoms.Conclusions. Therefore, follow-up and rehabilitation care for COVID-19 patients must be focused on addressing the needs of these people in the longer term.